2009
DOI: 10.17796/jcpd.33.4.83331867x68w120n
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactoperoxidase System Containing Toothpaste on Cariogenic Bacteria in Children with Early Childhood Caries

Abstract: Background and Objectives: Lactoperoxidase system contains Lactoperoxidase, Hydrogen peroxide and Thiocyanate ions, which have inhibitory action against cariogenic oral microflora. The present study was undertaken to assess the effect of lactoperoxidase system containing toothpaste on cariogenic microflora in children with early childhood caries. Methods: Study group included 30 children with Early Childhood Caries. 15 were considered as test group who used the test product Biotene® toothpaste and other 15 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…In our study, antimicrobial activity against S. mutans and L. acidophilus was observed only with Biotene Dry Mouth Oral Rinse and BioXtra gel, but no anti‐candidal effect was observed with any of our test materials. Both saliva substitutes contained peroxidase enzymes that may have antimicrobial effects on several microorganisms, including mutans streptococci, lactobacilli, fungi, and some viruses 2,31,32 . The function of sialoperoxidase (lactoperoxidase) in saliva has been reported at physiologic concentrations and with cofactors commonly found in saliva 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, antimicrobial activity against S. mutans and L. acidophilus was observed only with Biotene Dry Mouth Oral Rinse and BioXtra gel, but no anti‐candidal effect was observed with any of our test materials. Both saliva substitutes contained peroxidase enzymes that may have antimicrobial effects on several microorganisms, including mutans streptococci, lactobacilli, fungi, and some viruses 2,31,32 . The function of sialoperoxidase (lactoperoxidase) in saliva has been reported at physiologic concentrations and with cofactors commonly found in saliva 25 .…”
Section: Discussionmentioning
confidence: 99%
“…This constant source of HOSCN has been reported to inhibit acid production by glucose-stimulated plaque [40] and reduce growth of periodontopathic bacteria [41]. The LPO-SCN-glucose oxidase (GOX)-containing toothpaste Biotène has been reported to significantly increase SCN and reduce cariogenic bacteria load in 3–5-year olds treated for caries after 4 weeks of brushing compared to controls [42]. The commensal bacteria Streptococcus sanguinis , which is a normal component of the healthy human oral cavity flora, is among the strains of Streptococcus that have developed high expression of NADH-hypothiocyanite oxidoreductase that reduces OSCN − back to SCN.…”
Section: Biology Of Thiocyanatementioning
confidence: 99%
“…The mechanism behind the anti-microbial action of lactoperoxidase 476 has been established and forms the basis of applications for this bioactive whey protein (Boots & Floris, 2006;Kussendrager & van Hooijdonk, 2000). In particular, commercial quantities of 478 lactoperoxidase have allowed for this protein to be used in a range of oral healthcare products (Boots & Floris, 2006;Jyoti et al, 2009). Clinical trials have shown that lactoperoxidase is 480 efficacious in inhibiting bacteria associated with gingivitis, reducing inflammation and promoting the healing of gums, and reducing halitosis (Boots & Floris, 2006;Tenovuo, 2002).…”
Section: Page 21 Of 54mentioning
confidence: 99%
“…The anti-microbial properties of lactoperoxidase have also been exploited in toothpaste for young children so as to avoid the toxicity of fluoride prior to children learning not to swallow 484 fluoride-containing toothpastes (Jyoti et al, 2009). …”
Section: Page 21 Of 54mentioning
confidence: 99%